THE EFFECT OF EARLY MOBILIZATION ON REDUCING PAIN INTENSITY IN POST-CAESAREAN SECTION PATIENTS AT ALI SIBROH HOSPITAL, MALISI - Hikma, Wa Ode Erty; Mustikawati, Mustikawati; Rahmawati, Rizky; Rahmawati, Yunita (UNG, 2026)
Postoperative pain is a common problem experienced by patients after cesarean section and can hinder early mobilization, delay recovery, and reduce maternal comfort during the early postpartum period. Therefore, effective pain management is crucial and should not rely solely on pharmacological therapy, but also include safe and effective non-pharmacological nursing interventions. The novelty of this study lies in the implementation of structured and gradual early mobilization as an independent nursing intervention to reduce pain intensity in post-cesarean section patients at Ali Sibroh Malisi Hospital. This study aims to determine the effect of early mobilization on reducing pain intensity in post-cesarean section patients. A quantitative research method with a pre-experimental design using a one-group pretest-posttest approach was conducted. The sample consisted of 70 post-cesarean section patients selected through purposive sampling based on predetermined inclusion criteria. Pain intensity was measured before and after the intervention using a Numeric Rating Scale (NRS), which has demonstrated acceptable validity and reliability. Early mobilization was carried out in a structured and gradual manner according to patient tolerance. Data were analyzed using appropriate statistical tests to compare the average pain intensity before and after the intervention. The results showed a statistically significant reduction in pain intensity after early mobilization (p 0.05), indicating the effectiveness of this intervention in managing postoperative pain. In conclusion, early mobilization significantly reduces pain intensity in post-cesarean section patients and is recommended as a routine nursing intervention to accelerate recovery and improve the quality of nursing care.